Strategi Pembelajaran Pendidikan Pancasila dan Pendidikan Kewarganegaraan sebagai Mata Kuliah Pembentuk Karakter Mahasiswa - Anif Istianah; Sukron Mazid; Rini Puji Susanti (heritage, 2021)
The study is done to see how Pancasila Education and Civic Education subject strategies as a college education compulsory in character building sublime Pancasila students based on personality. Background research is related to problems that occur in the country: anarchism, radikalisme, terrorism, and other. These problems can undermine the unity of the Republic of Indonesia. The research is in University and the University of Muhammadiyah Purwokerto Tidar Nusa Cendana. But this research is qualitative descriptive method which is through observation, interview, and documentation. The validity of data over (trianggulasi) sources and methods. Data and analysis is by reduction, presentation of data, and the withdrawal of the conclusions. The result showed that Pancasila Education and Civic Education as subject to common (MKWU) at the University and the University of Muhammadiyah Purwokerto Tidar Nusa Cendana. The Subject has the role so important in the development of personality students in accordance with nilai-nilai Pancasila. It is seen in cognitive learning: achievement, psychomotor, affective. In reaching cognitive, students are taught some material relating to the reality in civil with Pancasila values. The objective is to students having knowledge based on good Pancasila. The psychomotor focused on learning skills students by using the method as a form of learning based on the kids. An affective seen in character students so far in accordance with Pancasila values.